2019
DOI: 10.1186/s12886-019-1192-0
|View full text |Cite
|
Sign up to set email alerts
|

A case of probable Vogt–Koyanagi–Harada disease in a 3-year-old girl

Abstract: Background Vogt–Koyanagi–Harada (VKH) disease is a T-cell-mediated autoimmune disorder characterized by bilateral granulomatous panuveitis with various systemic manifestations. Although VKH disease rarely occurs in the pediatric population, the clinical course tends to be aggressive, and the visual prognosis is worse than that in adult patients due to severe ocular complications secondary to recurrent inflammation. Case presentation A 3-year-old girl with probable VKH w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…Atsuko et al found that initial treatment with repeated high-dose intravenous corticosteroid therapy might benefit pediatric VKH disease [14]. Chee SP et al also found that higher doses of systemic corticosteroids may be required to ensure adequate immunosuppression in VKH patients [16].…”
Section: Discussionmentioning
confidence: 99%
“…Atsuko et al found that initial treatment with repeated high-dose intravenous corticosteroid therapy might benefit pediatric VKH disease [14]. Chee SP et al also found that higher doses of systemic corticosteroids may be required to ensure adequate immunosuppression in VKH patients [16].…”
Section: Discussionmentioning
confidence: 99%
“…11,12 After searching the PubMed and CiNii Research databases for cases of VKH disease (keyword, 'VKH'; search years, 2000-2022), to the best of our knowledge, the oldest reported cases of VKH disease were aged 83 years, 14,15 while the youngest reported cases were aged 3 years. [16][17][18] Because elderly individuals tend to have systemic diseases, consideration should be paid to side-effects associated with highdose systemic steroids. There are two reports about the side effects of steroid pulse therapy in elderly patients with VKH.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 After searching the PubMed and CiNii Research databases for cases of VKH disease (keyword, ‘VKH’; search years, 2000–2022), to the best of our knowledge, the oldest reported cases of VKH disease were aged 83 years, 14,15 while the youngest reported cases were aged 3 years. 1618…”
Section: Discussionmentioning
confidence: 99%
“…Multimodal imaging of pediatric VKH has been described in the literature in patients as young as 3 years of age, and demonstrates the utility of serial imaging for following the often aggressive disease course in children. Katsuyama et al 104 reported imaging findings of a 3-year-old girl with VKH using OCT, which demonstrated bilateral serous retinal detachments and choroidal thickening on presentation, persistence of subretinal fluid (SRF) despite two courses of high-dose intravenous corticosteroid therapy, and ultimate resolution of SRF and restoration of the ellipsoid zone after her third course of corticosteroid therapy. Khalifa et al 103 described a 12-year-old female patient who experienced improvement in serous detachments following treatment with infliximab and methotrexate treatment, but was found to have persistent submacular fluid on OCT and eventually required cyclophosphamide to achieve quiescence of inflammation.…”
Section: Imaging In Pediatric Uveitismentioning
confidence: 99%